Fracture behaviour of a Fe–22Mn–0.6C–0.2V austenitic TWIP steel. (October 2015) - Lorthios, Julie; Mazière, Matthieu; Lemoine, Xavier; Cugy, Philippe; Besson, Jacques; Gourgues-Lorenzon, Anne-Françoise
Abstract: The mechanical behaviour of a 22Mn–0.6C–0.2V austenitic TWIP steel has been extensively characterised for a variety of strain ratios (from shear to biaxial stretching) using smooth and notched specimens. A constitutive model involving a non-isotropic yield function together with isotropic and/or kinematic hardening satisfactorily represented the experimental database. It was used to estimate local stress and strain fields and to derive a fracture criterion based on the equivalent stress and Lode angle that were expressed to be consistent with the constitutive equations describing the plastic flow behaviour. A weak dependence on hydrostatic stress further improves prediction of fracture initiation, with an average standard error of less than 5% over ten different mechanical tests. Highlights: Plastic flow and fracture of TWIP steel are determined in various loading conditions. The plastic yield is well described by a Barlat criterion with non-linear hardening. Both carbides and mechanical twinning are involved in abrupt ductile fracture. Part of the (anisotropic) forming limit diagram is described by a simple criterion.